How Organizational Change Disrupts Our Sense of Self - Gregersen, Hal; Gregersen, Hal; Lehman, Roger (MIT Sloan Management Review, 2021)
Leaders driving transformation often focus too much on how employees' tasks will change -- but this is less of a hurdle for workers than dealing with the threat to the informal roles they've established. Major transitions cause personal disruption along three different dimensions: role adjustment, task learning, and emotional engagement. To better manage transformative change, leaders need to focus not only on how their own roles need to adapt, but also help employees adapt to new identities.